الحروف الزائدة ومعانيها في القرآن الكريم: دراسة تحليلية نحوية: Additional Letters and their meanings in Qur’an: An Analytical Grammatical Study - Atotileto, Abdus Salam; Dr. Uthman Abdussalam (Al Basirah, 2024)
In this article both the researchers show their great efforts to find out and collect “حروف المعاني الزائدة”; some letters that have no impact in the Arabic syntax. Therefore, to establish this impact therein and present it in a coordinated framework, is the basic premise that this article dwells upon. This research is based on two methods; the descriptive inductive method and the analytical method. Expression with “زائدة” is presented by the grammarians from Basrah and this terminology is commonly used in the books of grammar, Tafaseer and Qira’at. As for the Kufans, they express them with the terms of “الحشو (interpolation)” and “الصلة (connection)”. This research also finds that some scholars, interpreters of the Qur’an and grammarians, deny the existence of additional letters in the Qur’an. They gave such letters some other names i.e. “التأكيد” and “الصلة” etc. and they think that there are no additional letters in the Qur’an which have no meanings. They think that every letter in the Qur’an has its own meaning which it carries. They consider it as lack of manners to call Qur’anic letters “Zaidah (additional letters)” but grammarians do not see any problem in expressing them “Zaidah” and this terminology is commonly used in their books because they are more concerned with the aspect of syntax rather than the aspect of meaning.